# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime \prime \prime }-y^{\prime \prime }-8 y^{\prime }+12 y = X \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y = 3+{\mathrm e}^{-x}+5 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y = \left (1+{\mathrm e}^{x}\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = 3 \,{\mathrm e}^{\frac {5 x}{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+3 y^{\prime \prime }+2 y^{\prime } = x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+8 y = x^{4}+2 x +1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime \prime }-y^{\prime }-y = \cos \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+a^{2} y = \cos \left (a x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y = 2 \sin \left (\frac {x}{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y = \sin \left (3 x \right )-\cos \left (\frac {x}{2}\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+y = {\mathrm e}^{2 x} x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }+2 y = \sin \left (x \right ) {\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y = x^{2} {\mathrm e}^{3 x}+{\mathrm e}^{x} \cos \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = x \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = x^{2} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (5\right )}-13 y^{\prime \prime \prime }+26 y^{\prime \prime }+82 y^{\prime }+104 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+2 y^{\prime \prime }+y^{\prime } = {\mathrm e}^{2 x}+x^{2}+x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = \sin \left (3 x \right )+{\mathrm e}^{x}+x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-5 y^{\prime }+6 y = x +{\mathrm e}^{m x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-a^{2} y = {\mathrm e}^{a x}+{\mathrm e}^{n x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime \prime }-6 y^{\prime }+8 y = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+y^{\prime \prime \prime }+y^{\prime \prime } = x^{2} \left (b x +a \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-13 y^{\prime }+12 y = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 n^{2} y^{\prime \prime }+n^{4} y = \cos \left (m x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 y^{\prime \prime }+y = x^{2} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+a^{2} y = \sec \left (a x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = x^{2} {\mathrm e}^{3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+n^{2} y = {\mathrm e}^{x} x^{4}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-a^{4} y = x^{4}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-2 y^{\prime \prime \prime }+y^{\prime \prime } = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-y = {\mathrm e}^{x} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-7 y^{\prime }-6 y = {\mathrm e}^{2 x} \left (1+x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+4 y = {\mathrm e}^{x} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+3 y^{\prime \prime }+3 y^{\prime }+y = {\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-2 y^{\prime \prime \prime }-3 y^{\prime \prime }+4 y^{\prime }+4 y = {\mathrm e}^{x} x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime \prime }+3 y^{\prime }-y = x \,{\mathrm e}^{x}+{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = x \sin \left (x \right )+\left (x^{2}+1\right ) {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+3 y = {\mathrm e}^{x} \cos \left (2 x \right )+\cos \left (3 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime \prime }+4 y^{\prime }-2 y = {\mathrm e}^{x}+\cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-9 y^{\prime }+20 y = 20 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime \prime }+4 y = {\mathrm e}^{3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y = \sin \left (x \right ) {\mathrm e}^{2 x}+{\mathrm e}^{\frac {x}{2}} \sin \left (\frac {\sqrt {3}\, x}{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime } = x \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = x^{2} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+a^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+a^{2} y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (5\right )}-m^{2} y^{\prime \prime \prime } = {\mathrm e}^{a x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-a^{2} y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = \frac {a}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime } = \sin \left (x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}a y^{\prime \prime } = y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime } = f \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-n^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-2 y^{\prime \prime }-y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{\prime \prime }+5 x^{\prime }-12 x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }-54 y = 0
\] |
✓ |
✓ |
|
\[
{}9 x^{\prime \prime }+18 x^{\prime }-16 x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime \prime }-5 y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime \prime }+3 y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-2 y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+8 y^{\prime \prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+3 y^{\prime \prime }+y^{\prime }-5 y = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime \prime }-3 y^{\prime \prime }+2 y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-5 y^{\prime }+6 y = {\mathrm e}^{4 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = 2+5 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }-15 y = 15 x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sec \left (x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = 2 \,{\mathrm e}^{\frac {5 x}{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = {\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 p y^{\prime }+\left (p^{2}+q^{2}\right ) y = {\mathrm e}^{k x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = \sin \left (2 x \right )+\cos \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+a^{2} y = \cos \left (a x \right )+\cos \left (b x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = {\mathrm e}^{x}+\sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+3 y^{\prime \prime }-y^{\prime }-12 y = \cos \left (4 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y = 2 \sin \left (\frac {x}{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sin \left (3 x \right )-\cos \left (\frac {x}{2}\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-4 y^{\prime \prime }+5 y^{\prime }-2 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y^{\prime \prime }-y^{\prime }+y = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y^{\prime \prime }-6 y^{\prime } = x^{2}+1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+2 y^{\prime \prime }+y^{\prime } = {\mathrm e}^{2 x}+x^{2}+x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime }+2 y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+5 y = \sin \left (x \right ) {\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+4 y = {\mathrm e}^{x} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = \cosh \left (x \right ) \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-7 y^{\prime }-6 y = {\mathrm e}^{2 x} \left (1+x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+y^{\prime \prime }+y = a \,x^{2}+b \,{\mathrm e}^{-x} \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }-12 y = \left (x -1\right ) {\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = x \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 y^{\prime \prime }+y = x^{2} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-y = x \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = x \,{\mathrm e}^{x} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+4 y = 8 x^{2} {\mathrm e}^{2 x} \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = {\mathrm e}^{-x}+\cos \left (x \right )+x^{3}+{\mathrm e}^{x} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+y^{\prime \prime }+y = {\mathrm e}^{-\frac {x}{2}} \cos \left (\frac {\sqrt {3}\, x}{2}\right )
\] |
✓ |
✓ |
|